Do androids dream of electric sheep? - Dick, Philip K. (London : Gollancz, 2007)
In January 2021, years after World War Terminus has destroyed the planet, bounty hunter Rick Deckard remains on the Earth pursuing his vocation of hunting down and killing rogue androids.
Young Adult.
Young Adult
Keywords: Androids -- Fiction; Robots -- Fiction; Science fiction